The exploration of indigenous plant-based coagulant for sumbawanese cheese production as probiotic source - Ariskanopitasari, Ariskanopitasari; Rizaldi, Lalu Heri; Sari, Ratna Nurmalita (Universitas Muhammadiyah Mataram, 2023)
Sumbawa cow's milk processing is still limited even though it has the potential to be developed. Therefore, a diversification product like cheese as a source of probiotic is required. Cheese derived from milk that is coagulated using rennet which is expensive and has high halal critical point. Thus, an alternative coagulant that is affordable with low halal critical point such as local plant-based material is needed. This study used Sumbawa local cow’s milk to produce cheese which coagulated using pineapple and gooseberry and the addition of Lactobacillus lactis as the lactic acid bacteria. Observed parameters were clotting time, yield, hardness, protein, total fat, total lactic acid bacteria, and sensory quality. This experiment showed that the cheese yielded using pineapple was higher than that of gooseberry, while the cheese coagulated using gooseberry (26714 N/m2) was having firmer texture. Meanwhile, clotting time, protein content and total fat content of the cheese coagulated using both coagulants were the same. The total lactic acid bacteria of the cheese coagulated using pineapple and gooseberry was similar 10.80 Log CFU/mg and 10.84 Log CFU/mg, respectively. Sensory evaluation using quantitative descriptive analysis showed that the cheese coagulated using pineapple extract has higher aftertaste and bitter taste. Meanwhile, the cheese coagulated using gooseberry extract was dry, grainy, yellowish, and its overall acceptance was higher than that of pineapple.